(untitled) (Indian Journal of Arid Horticulture, 2025)
A field experiment to study the effect of crop geometry and fertility levels on growth, yield and quality of kharif onion was conducted at Horticulture Farm, SKN College of Agriculture, Jobner during kharif seasons of 2001 and 2002. Plant spacing 45cm x 10 cm was superior over different spacing in relation to growth (number of leaves plant’, fresh and dry weight of leaves), yield attributes (neck thickness, neck length, equatorial diameter, polar diameter, number of scales bulb’, fresh weight and volume of bulb) and quality attributes (N, P and K in bulb). Yield of bulbs was maximum at 30 cm x 10 cm spacing. Fifty per cent recommended dose of NPK + vermicompost 2.5 t ha significantly improved the growth, yield and quality attributes (pungency and vitamin C) over rest of the treatments.